Developing a High-Impact Learning Program for Global Health Professionals: The STAR Project. (March 2020) - Hansoti, Bhakti; Schleiff, Meike; Akridge, Anike; Dolive, Caroline; Gordon, Angelina; Rodríguez, Daniela C.; Hausner, David; Pariyo, George; Quinn, Thomas; Rudy, Sharon; Tackett, Sean; Bennett, Sara
Background. The Sustaining Technical and Analytical Resources (STAR) project seeks to invest in and expand the capacity of diverse senior global public health professionals. STAR builds on traditional work-based fellowships by partnering with universities in order to curate (or develop) and deliver high-quality, tailored learning across a set of required "core competency domains" as well as elective skills- or content-based competency domains. Pedagogy. In a rapidly changing global health context, ongoing learning is essential but often gets sidelined by other pressures; STAR's approach aims to respond to these challenges by developing a learning curriculum tailored to the needs of our participants and their roles in global health. STAR's pedagogy utilizes individualized learning plans, a deliberate practice approach, and a hybrid mentorship model to support project participants to achieve their learning objectives as well as broader project goals. Next Steps. The STAR project is in its first year of implementation. Furthermore, our future work will focus on developing a monitoring and evaluation plan that seeks to track the progress of our participants, guide project improvements, measure the impact of learning activities, and inform the pedagogy of future global health training initiatives.